Ubuntu, Migration and Ministry : Being Human in a Johannesburg Church. - Hankela, Elina (Studies in Systematic Theology., 2014)
In Ubuntu, Migration and Ministry Elina Hankela engages with the socio-moral meanings of ubuntu (Nguni: humanness/humanity) in contemporary Johannesburg drawing on ethnographic fieldwork at the Central Methodist Mission, a Johannesburg inner-city church that has been re-shaped in the face of international migration.